Exploring Tax Accounting Rules and Their Influence on Financial Reporting - Muslim, Muslim (Advances in Taxation Research, 2024)
Purpose: This study explores the complex relationship between tax accounting rules and financial reporting outcomes, focusing on the determinants of effective tax rates (ETRs) and the implications of tax planning strategies on financial reporting integrity. Research Design and Methodology: This research uses a systematic literature review approach to analyze findings from theoretical perspectives and empirical studies in accounting, economics, law, and management. Findings and Discussion: The research identifies critical determinants of ETRs, including industry characteristics, firm size, profitability, tax planning strategies, and corporate governance mechanisms. In addition, the study examines the implications of tax planning strategies on the integrity of financial reporting, considering the perspectives of agency theory, signaling theory, and regulation. Implications: The findings emphasize the importance of considering industry-specific dynamics, governance mechanisms, and regulatory interventions in evaluating corporate tax compliance behavior and financial reporting practices. This research provides evidence-based insights for policymakers, regulators, practitioners, and academics to design effective regulatory frameworks and compliance strategies, supporting transparency and accountability in financial reporting practices.